Comparative evaluation of high flow oxygen therapy versus low flow oxygen therapy in the management of acute moderate bronchiolitis - A., Pragalatha Kumar; Sajjanar, Sujata (International Journal of Contemporary Pediatrics, 2023)
Background: Acute bronchiolitis is the most common respiratory tract infection in young children. Despite the high prevalence, no consensus exists on management. Hence the present study was conducted to find out the efficacy of high flow oxygen therapy (HFNC) versus low flow oxygen therapy in the management of acute moderate bronchiolitis. Methods: Prospective randomized controlled study of 100 children aged between 2 months to 24 months with signs and symptoms of acute moderate bronchiolitis were admitted to Indira Gandhi Institute of Child Health, Bangalore from January 2018 to June 2019 formed the study group, they were randomised into 2 groups, group A received high flow oxygen therapy and group B received low flow oxygen therapy. Results: Out of 100 children enrolled in the study, 50 children (group A) received high flow oxygen therapy and 50 children (group B) received low flow oxygen therapy. At 24 hours the mean severity score for group A was 0.46±077 and group B was 1.86±0.86 (p<0.001). Maximum improvement in O2 saturation was observed in group A compared to group B. The duration of hospital stay was shorter (2-3 days) in group A with a mean of 2.20 days and was longer (4-5 days) in group B with a mean value of 3.84 days which was statistically significant (p<0.001). Conclusions: Children with acute bronchiolitis treated with heated humidified high flow oxygen (HFNC) had early improvement in the clinical severity score, reduced duration of oxygen requirement and decrease in the length of hospital stay. Hence heated humidified high flow oxygen (HFNC) is an effective and safe modality of treatment for children with acute moderate bronchiolitis compared to low flow oxygen therapy (p<0.0001).